Pengaruh Perubahan Kurikulum di SDN 01 Pandasari, Kecamatan Warungasem, Kabupaten Batang, Provinsi Jawa Tengah - Sekar Wulan; Alfinatur Rosyidah; Anisah Hania; Abidatul Karimah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to investigate the effect of curriculum changes at SDN 01 Pandasari, Warungasem District, Batang Regency, Central Java Province on the quality of education and student learning outcomes. The research method used was interviews with teachers, principals, and parents of students as respondents. Interview data were analyzed using qualitative analysis techniques, such as thematic analysis. In addition, secondary data from the documentation was also collected to gain a more complete understanding of curriculum changes and their impact on the quality of education and student learning outcomes. The results of the research show that curriculum changes have a positive impact on the quality of education and student learning outcomes, but also pose a number of challenges that need to be addressed. Efforts that have been made to overcome these challenges include teacher training and development, improving school facilities, and increasing communication with students' parents.